Controle e profilaxia da mastite bovina - Oliveira, Luiza Bruna Passerini Barreiro de [UNESP] (2017)
Brazil was the fifth largest producer of milk in the world in 2015. However, the increase in milk production must be related to the quality of the product. In this sense, attention must be paid to the occurrence of bovine mastitis. This inflammation in the mammary gland of cows is responsible for most economic losses in dairy cattle, with Staphylococcus aureus as its main etiological agent. Aiming at the importance of this disease for both dairy production costs and public health and animal health, this review aims to report the importance of applying measures of prophylaxis of bovine mastitis through the use of diagnostic methods, hygiene measures and treatments